ROP examination of premature babies at an eye hospital referred from urban and semi-urban NICUs - Venkatesh, Ramesh; Dave, Prachi Abhishek; Gurav, Prachi; Agarwal, Manisha; Jajoo, Mamta; Gupta, Vidit (Nepalese Journal of Ophthalmology, 2020)
Introduction: Retinopathy of prematurity (ROP) is seen in low gestational age (GA) and birth weight (BW) babies leading to retinal vascular damage. Screening of preterm would help in early identification of this, sight-threatening disease. Multiple factors play an important role in planning screening strategies for these preterm. The objective of this study was done to find the differences and the reasons affecting the proportion of ROP distribution between urban and semi-urban regions in North India. Materials and methods: In this retrospective, comparative study, all babies referred for ROP examination by paediatricians or other general ophthalmologists between 2013 to 2016 were included in the study. Demographic, clinical and treatment related findings were recorded. Results: Five hundred and fifty eight babies (467: urban and 91: semi urban) were examined for ROP. The mean BW in urban and semi-urban settings was 1348.6 ± 395.21 gm and 1703.77 ± 401.76 gm respectively. The mean GA was 30.99 ± 2.93 weeks and 30.73 ± 2.08 weeks in the urban and semi-urban cohorts respectively. The average time for first ophthalmic examination following birth was 23.82 ± 13.69 (range: 3-77) days in urban and 101.16 ± 238.26 (range: 13- 330) days in semi-urban settings. 94% of the babies completed all screening examination visits. Any ROP was identified in 12% and 33.0% of urban and semi-urban cohorts respectively; Type 1 was detected in 7.5% of urban babies and 24% of semi-urban babies. Conclusion: Proportion of ROP in the urban region was 3 times lesser than the semiurban region. Differences in proportion of babies developing any ROP and Type 1 ROP between semi-urban and urban groups is likely due to selection bias, as a high proportion of semi-urban babies did not attend for examination or failed to complete all the examinations necessary. This was particularly true for females. More needs to be done to increase access to regular, systematic screening of preterm babies within neonatal units.